Atmospheric CO2 Alters Resistance of Arabidopsis to Pseudomonas syringae by Affecting Abscisic Acid Accumulation and Stomatal Responsiveness to Coronatine - Zhou, Yeling; Vroegop-Vos, Irene; Schuurink, Robert C.; Pieterse, Corné M. J.; Van Wees, Saskia C. M. (Frontiers in Plant Science, 2017)
Atmospheric CO2 influences plant growth and stomatal aperture. Effects of high or low CO2 levels on plant disease resistance are less well understood. Here, resistance of Arabidopsis thaliana against the foliar pathogen Pseudomonas syringae pv. tomato DC3000 (Pst) was investigated at three different CO2 levels: high (800 ppm), ambient (450 ppm) and low (150 ppm). Under all conditions tested, infection by Pst resulted in stomatal closure within 1 h after inoculation. However, subsequent stomatal reopening at 4 h, triggered by the virulence factor coronatine (COR), occurred only at ambient and high CO2, but not at low CO2. Moreover, infection by Pst was reduced at low CO2 to the same extent as infection by mutant Pst cor-. Under all CO2 conditions, the ABA mutants aba2-1 and abi1-1 were as resistant to Pst as wild-type plants under low CO2, which contained less ABA. Moreover, stomatal reopening mediated by COR was dependent on ABA. Our results suggest that reduced ABA levels at low CO2 contribute to the observed enhanced resistance to Pst by deregulation of virulence responses. This implies that enhanced ABA levels at increasing CO2 levels may have a role in weakening plant defense.